IDDF2019-ABS-0094 Tumor size and location affecting the treatment selection for solitary small recurrent hepatocellular carcinoma (≤3.0 cm) after initial hepatectomy. (June 2019) - Chen, Shuling; Peng, Zhenwei; Xiao, Han; Wei, Mengchao; Kuang, Ming
Abstract : Background: We aimed to investigate the optimal treatment modality between radiofrequency ablation (RFA) and repeated hepatectomy in the treatment of solitary recurrent HCC (rHCC) after hepatectomy, considering the influence of tumor size and location. Methods: From Jan 2009 to Dec 2016, 630 consecutive patients with solitary small rHCC (≤3.0 cm) after initial hepatectomy who underwent RFA or repeated hepatectomy were enrolled in three tertiary referral centers. Patients were divided into four groups according to tumor size (≤ 2.0 cm or >2.0 cm) and location (central or peripheral) respectively. Overall survival (OS) and recurrence-free survival (RFS) rates were compared between RFA and repeated hepatectomy in these four groups. Results: For central rHCC ≤ 2.0 cm, the OS and RFS rates at 5 years after RFA were significantly higher than those after repeated hepatectomy (69.9% vs 53.1%, P=0.001; 56.2% vs 42.6%, P=0.038). For central rHCC >2.0 cm, the 5-year OS and RFS rates were not significantly different between repeated hepatectomy and RFA (55.9% vs 48.2%, P=0.080; 27.0% vs 19.2%, P=0.103). For peripheral tumors ≤ 2.0 cm (58.8% vs. 47.7%, P=0.001; 45.2% vs. 25.6%, P=0.001) or >2.0 cm (62.6% vs. 45.4%, P=0.001; 44.7% vs. 21.1%, P=0.010), the OS and RFS rates at 5 years after repeated hepatectomy were both significantly higher than those after RFA. Complications were more common in patients after repeated hepatectomy than RFA, especially for central tumors. Conclusions: RFA might be the optimal treatment for patients with central rHCC ≤ 2.0 cm whereas repeated hepatectomy should be recommended for patients with peripheral tumors.